Creeping through the cranium: A rare and interesting presentation of a meningioma - Jayanthraj Gone, DO; Brittany Kennedy, DO; Tyler Fontaine, DO; Sandor Szilagyi, MD (Radiology Case Reports, 2024)
A meningioma is a rare primary CNS tumor that tends to present more so in females in a slowly progressive fashion. The cavernous sinus and cerebellopontine angle are uncommon locations for meningiomas. We present a case of a meningioma in a 60-year-old female presenting to the emergency department for a sudden onset headache, vertigo, facial paresthesias, and chest pain. Inpatient workup revealed orthostatic hypotension, a meningioma spanning from the left cavernous sinus to the left cerebellopontine angle encasing the left cavernous internal carotid artery on MRI and CTA, and an incidental 12 mm calcified fibroadenoma on CT. Hospital course consisted of supportive treatment, physical rehabilitation, and review of previous imaging to determine need for intervention per consultants’ recommendations. The patient was discharged with an antiplatelet, an antihistamine, appropriate additional medications, a vestibular therapy script, and outpatient referrals for a decision regarding surveillance and intervention. Overall, this case describes some key points. It demonstrates that cavernous sinus and cerebellopontine angle meningiomas can occur simultaneously, especially as a continuous mass, which very few cases have done so far. It also highlights an acute clinical presentation of a meningioma, contrary to the gradually progressive one observed in most instances. Last, but not least, it shows how nonspecific symptoms can lead to unique findings at times.